Given that 2 x = x 2 6 5 5 2 0 , find the value of lo g 2 ( lo g 2 x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Judging from your solution I gather you meant the equation in the question to be
2 x = x 2 6 5 5 2 0 .
Problem Loading...
Note Loading...
Set Loading...
Taking the base-2 logarithm of both sides of the original equation gives
x = 2 6 5 5 2 0 lo g 2 x
doing so again gives
lo g 2 x = 6 5 5 2 0 + lo g 2 ( lo g 2 x )
Note that 2 1 6 = 6 5 5 3 6 = 6 5 5 2 0 + 1 6
And letting lo g 2 ( lo g 2 x ) = 1 6 so that lo g 2 x = 6 5 5 3 6 we get a perfect solution so indeed
lo g 2 ( lo g 2 x ) = 1 6